Magnetic phase transitions in the NdFe₃(BO₃)₄ multiferroic - Zvyagina, G.A.; Zhekov, K.R.; Bilych, I.V.; Zvyagin, A.A.; Gudim, I.A.; Temerov, V.L. (Физика низких температур, 2011)
Low-temperature studies of the behavior of the sound velocity and attenuation of acoustic modes have been performed on a single crystal NdFe₃(BO₃)₄ Transitions of the magnetic subsystem to the antiferromagnetically ordered state at TN ≈ 30.6 K have been revealed in the temperature behavior of the elastic characteristics. The features in the temperature behavior of elastic characteristics of the neodymium ferroborate and its behavior in the external magnetic field, applied in the basic plane of the crystal, permit us to suppose that the transition to an incommensurate spiral phase is realized in the system. This phase transition behaves as the first order one. H–T phase diagrams for the cases H || a and H || b have been constructed. The phenomenological theory, which explains observed features, has been developed.